AB0741 ACHIEVEMENT OF CDAPSA LOW DISEASE ACTIVITY OR REMISSION IS ASSOCIATED WITH CONTROL OF ARTICULAR AND EXTRA-ARTICULAR MANIFESTATIONS OF ACTIVE PSORIATIC ARTHRITIS IN SUBJECTS TREATED WITH APREMILAST. (June 2019) - Coates, Laura C.; Mease, Philip J.; Behrens, Frank; Orbai, Ana-Maria; Ogdie, Alexis; Brunori, Michele; Teng, Lichen; Guerette, Benoit; Smolen, Josef S.
Abstract : Background: Therapeutic targets for psoriatic arthritis (PsA) include the achievement of remission (REM) or low disease activity (LDA), measured by the Clinical Disease activity index for Psoriatic arthritis (cDAPSA [0-154]), a composite of swollen and tender joints counts (SJC and TJC), Patient's assessment of Pain (PAP) and Patient's Global assessment of Disease activity (PtGA). Objectives: We examined the trajectories for improvement in cDAPSA, its core components and PsA manifestations not measured by cDAPSA among subjects achieving cDAPSA REM or LDA by Week 52. Methods: Pooled analyses of the phase III PALACE 1, 2 and 3 studies were performed for subjects assigned to receive apremilast (APR) 30 mg twice daily at baseline (BL). Subjects with cDAPSA components available to calculate responses at Week 52 were included and grouped according to the cDAPSA categories reached at Week 52 (REM: ≤4; LDA: >4 to ≤13; moderate disease activity: >13 to ≤27; high disease activity: >27). We then traced their mean cDAPSA trajectory from BL to Week 52. Mean disease activity in core PsA domains were reported longitudinally by cDAPSA category reached at Week 52. Results: A total of 375 aPR subjects were included in the analyses. Achievement of REM or LDA by Week 52 was associated with lower mean cDAPSA at BL, and these subjects had continuous improvements in disease activity from BL to Week 52 (Figure). Among subjects who achieved REM or LDA by Week 52, most were classified as having LDA (mean cDAPSA: 8.5) or moderate disease activity (mean cDAPSA: 16.6), respectively, at Week 16. Furthermore, subjects who achieved REM or LDA by Week 52 showed early improvement, with no/mild articular and extra-articular disease activity by Week 52 with aPR (Table). Conclusion: In the subgroup of subjects who achieved cDAPSA REM or LDA, early improvement was seen in disease activity by Week 16 and sustained to Week 52 with continued treatment. Subjects achieving cDAPSA REM or LDA exhibited no or mild disease activity in enthesitis, dactylitis, function and skin psoriasis by Week 52. Disclosure of interests: Laura C Coates Grant/research support from: abbVie, Celgene, Lilly, Novartis and Pfizer, Consultant for: abbVie, amgen, BMS, Celgene, Galapagos, Gilead Sciences inc., Janssen, Lilly, Novartis, Pfizer, Prothena Corp and UCB, Philip J Mease Grant/research support from: abbVie, amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: abbVie, amgen, BMS, Galapagos, Gilead Sciences, inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: abbVie, amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Frank Behrens Grant/research support from: abbVie, Pfizer, Roche, Chugai, Prophylix, Bioline, Novartis, Consultant for: abbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, MSD, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, Speakers bureau: ad board: abbVie, Pfizer, Roche, Chugai, UCB, Bristol-Myers Squibb, Celgene, Novartis, Biotest, Janssen, Genzyme, Eli Lilly, ana-Maria Orbai Grant/research support from: abbVie, Celgene, Horizon Pharma, Janssen, Lilly, and Novartis, Consultant for: Lilly, Janssen, Novartis, Pfizer, and UCB, alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: abbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: abbVie, amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer inc, Takeda, Consultant for: abbvie, amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: abbvie, amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Michele Brunori Employee of: Celgene Corporation, Lichen Teng Employee of: Celgene Corporation, Benoit Guerette Employee of: Celgene Corporation, Josef S. Smolen Grant/research support from: abbVie, Eli Lilly, Janssen, MSD, Pfizer, Roche, Consultant for: abbVie, amgen, astra-Zeneca, astro, Celgene Corporation, Celtrion, Eli Lilly, Glaxo, ILTOO, Janssen, MedImmune, MSD, Novartis, Pfizer, Roche, Samsun, Sanofi, UDB, Speakers bureau: abbVie, amgen, astra-Zeneca, astro, Celgene Corporation, Celtrion, Eli Lilly, Glaxo, ILTOO, Janssen, MedImmune, MSD, Novartis, Pfizer, Roche, Samsun, Sanofi, UDB